A new coumarin from stem bark of Mesua hexapetala. Issue 14 (17th July 2016) - Karunakaran, Thiruventhan; Ee, Gwendoline Cheng Lian; Teh, Soek Sin; Daud, Shaari; Mah, Siau Hui; Lim, Chan Kiang; Jong, Vivien Yi Mian; Awang, Khalijah
Abstract: A new alkylated coumarin derivative, hexapetarin (1 ) along with three other xanthones, trapezifolixanthone (2 ), cudraxanthone G (3 ) and 1, 3, 7-trihydroxy-2, 4-di (3-methyl-2-butenyl)xanthone (4 ), and four common triterpenoids, friedelin(5), stigmasterol(6), beta-sitosterol(7) and gamma-sitosterol(8) were isolated from the stem bark of Mesua hexapetala (Clusiaceae), a plant, native to Malaysia. The structures of these compounds were elucidated and determined using spectroscopic techniques such as NMR and MS. Anti-inflammatory activity assay indicated hexapetarin (1 ) to possess moderate anti-inflammatory activity, while 1, 3, 7-trihydroxy-2, 4-di (3-methyl-2-butenyl)xanthone (4 ) gave very good activity. Abstract : A new alkylated coumarin derivative, hexapetarin (1) along with three other xanthones, trapezifolixanthone (2), cudraxanthone G (3) and 1, 3, 7-trihydroxy-2, 4-di (3-methyl-2-butenyl)xanthone (4) were isolated from the stem bark of Mesua hexapetala (Clusiaceae). The structures of these compounds were elucidated and determined using spectroscopic techniques such as NMR and MS.